Association between Serum C-reactive Protein and Pre-eclampsia (Faridpur Medical College Journal, 2021)
Among the common disorders of pregnancy, Pre-eclampsia is important one which causes significant maternal and perinatal morbidity and mortality. Its incidence is still high in the developing countries. The triad of high blood pressure, edema and albuminuria is neither specific nor sensitive enough; therefore, a reliable biochemical marker is needed to solve the problem. C-reactive protein(CRP), a marker of tissue damage and inflammation, is elevated in serum in overt preeclampsia. The present study is aimed to explore the association of high maternal serum C-reactive protein (CRP) level with preeclampsia and correlation with the severity of pre-eclamptic process. A total of 60 pregnant women constituting 30 pre-eclamptic (case) and 30 normal (control) pregnant women in the third trimester were enrolled in this study. Both the groups were matched for their age, parity and other baseline characteristics. More than three quarters (76.70%) of the case group exhibited raised serum CRP, which was 20% in control group (p=0.001). CRP was elevated about 13 fold higher than that in the normal pregnant women. The mean systolic and diastolic blood pressure were significantly higher in case group (154±12 mm of Hg) vs (107±7 mm of Hg) in control group (p